2018
DOI: 10.1136/bjsports-2017-098948
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of injuries in outdoor and indoor hockey players over one season: a prospective cohort study

Abstract: Hockey players have a high prevalence and incidence of injuries, especially at the lower limb.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 43 publications
3
32
4
Order By: Relevance
“…Although a previous study of field hockey suggested 36.2% (95%CI: 24.0‐49.9) of injuries are transient, we found the proportion to be 53.8% (95% CI: 46.0‐61.4). However, the distribution of injuries to the thigh, knee, and ankle was consistent with our study.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Although a previous study of field hockey suggested 36.2% (95%CI: 24.0‐49.9) of injuries are transient, we found the proportion to be 53.8% (95% CI: 46.0‐61.4). However, the distribution of injuries to the thigh, knee, and ankle was consistent with our study.…”
Section: Discussioncontrasting
confidence: 99%
“…16,26,27 Other studies classified severity based upon whether or not the injury caused a stoppage in time during the game. 28 Although a previous study of field hockey suggested 36.2% (95%CI: 24.0-49.9) of injuries are transient, 29 we found the proportion to be 53.8% (95% CI: 46.0-61.4). However, the distribution of injuries to the thigh, knee, and ankle was consistent with our study.…”
Section: Discussioncontrasting
confidence: 83%
“…In 1964, the International Hockey Federation (FIH) had 50 countries with affiliated national associations, and by 2019, this had increased to 137 . However, injuries are common, with half of all field hockey athletes reporting injuries of the upper and lower limbs and 10%‐68% reporting injuries of the head and face . The specific prevalence of orofacial injury due to playing field hockey ranges from 11% to 32%, but this data excludes cases of pain in the temporomandibular joints (TMJs) or masticatory muscles.…”
Section: Introductionmentioning
confidence: 99%
“…Second, match exposure time was calculated as the duration of the official matches (40 min with stopped clock/60) by number of athletes playing at the same time on the court [16], without counting warm-up of matches. Friendly matches were also included as match play exposure [17]. Additionally, injury prevalence was also calculated [18].…”
Section: Methodsmentioning
confidence: 99%